Peran Strategis Guru Pendidikan Agama Islam dalam Menangani Bullying di Madrasah Ibtida’iyah: The Strategic Role of Islamic Religious Education Teachers in Handling Bullying at Islamic Elementary School - Kharisma Miftahul Jannah; Muhammad Hasyim (Madrasah Tsanawiyah DDI Cilellang, 2025)
Bullying remains a pressing issue in Islamic elementary school (madrasah ibtidaiyah), institutions that are normatively expected to nurture students’ intellectual, emotional, spiritual, and moral growth. This condition highlights a significant gap between the ideal vision of Islamic education in shaping insan kamil and the practical realities observed in the school environment. This study aims to (1) analyze the forms of bullying occurring at madrasah ibtidaiyah, (2) identify contributing factors, and (3) explore the strategic roles of Islamic Religious Education (PAI) teachers in addressing and preventing bullying. Employing a qualitative descriptive case study, data were collected through participant observation, semi-structured interviews with teachers and students, as well as document analysis, and validated through triangulation and member checks. Findings indicate that bullying manifests primarily in physical and verbal forms, driven by social dominance dynamics, peer pressure, lack of parental supervision, and the influence of social media. PAI teachers play a pivotal role through value-based education, restorative mediation using dakwah bi al-hikmah, collaboration with families, and religion-based counseling programs. These strategies foster empathy, solidarity, and justice, contributing to a safer and more inclusive school environment. The study implies that anti-bullying programs in Islamic schools must be preventive, holistic, and contextually grounded in religious values, supported by collaboration among teachers, families, and communities. Nevertheless, the study is limited by its single-site focus, reliance on qualitative data, and the absence of direct parental perspectives, which constrain generalizability. Future research should adopt mixed methods and broader institutional comparisons to deepen understanding of bullying prevention in Islamic education.